2006
DOI: 10.1375/acri.39.3.371
|View full text |Cite
|
Sign up to set email alerts
|

Social Exclusion, Youth Transitions and Criminal Careers: Five Critical Reflections on ‘Risk’

Abstract: This paper draws upon recent youth research in some of Britain"s poorest neighbourhoods (in Teesside, North East England). It stresses the importance of a qualitative, biographical and long-term perspective in attempting to understand drugusing and criminal careers (and wider youth transitions) and points to some difficulties in applying -straightforwardly -influential models of risk assessment and prediction to individual biographies.In a context of deep, collective disadvantage, most research participants sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…Contemporary criminological research has prioritised eliciting the voices of children who offend to investigate how they experience, construct and negotiate ‘risk’ in qualitative, personally meaningful ways (cf. the Edinburgh Study – McAra and McVie, 2007, 2015; the Teesside Studies – Macdonald, 2007; the ESRC Pathways projects – France and Homel, 2007). Evidence-based constructivist understandings of how children negotiate and resist ‘pathways’ into and out of offending have subsequently influenced children first policy formations in Wales (e.g.…”
Section: Research-led Pathwaysmentioning
confidence: 99%
“…Contemporary criminological research has prioritised eliciting the voices of children who offend to investigate how they experience, construct and negotiate ‘risk’ in qualitative, personally meaningful ways (cf. the Edinburgh Study – McAra and McVie, 2007, 2015; the Teesside Studies – Macdonald, 2007; the ESRC Pathways projects – France and Homel, 2007). Evidence-based constructivist understandings of how children negotiate and resist ‘pathways’ into and out of offending have subsequently influenced children first policy formations in Wales (e.g.…”
Section: Research-led Pathwaysmentioning
confidence: 99%
“…Even when individuals of similar socio-economic backgrounds and circumstances were presented with similar risks, their responses were different, further reinforcing the criticism that risk factors are poor predictors and pathways are unpredictable (Hine 2006). The reality was that 'stuff happened' (Hine 2006;Webster 2005in MacDonald 2006 in the lives of young people and responses were often different to expectations given the findings of other risk-based criminal careers research. By providing a brief insight into the circumstances of young people's lives and their offending behaviour, something of the nature of the 'choices' open to young people are revealed.…”
Section: Critical Moments and Criminal Careersmentioning
confidence: 99%
“…Further, in calculating or measuring involvement in crime over a person's life span less attention is paid to the nature and circumstances of that offending behaviour. Consequently, the social, historical and indeed spatial context of offending is often lost or under-played (see MacDonald 2006), and other external influences that impact on criminal careers -such as contact with the criminal justice system -are ignored (France 2007).…”
Section: Introduction: Young People Risk and Regulationmentioning
confidence: 99%
“…The power-knowledge effect of the risk-factor paradigm also became particularly apparent when further considering one of its key points of critique, namely, the individualisation of offending behaviour at the expense of a consideration of wider societal factors (France, 2008;Gray, 2007Gray, , 2009Gray, , 2011Hannah-Moffat, 1999;Kemshall, 2008;Mac Donald, 2006). A closer look at the risk factors adopted, for example, in the Baseline Analysis (IYJS, 2009) showed that they were all formulated with the effect of individualising young people's offending behaviour.…”
Section: Fabricating Risk and Emphasising Deficitsmentioning
confidence: 99%